An insight into the reaction mechanism of CO2 photoreduction catalyzed by atomically dispersed Fe atoms supported on graphitic carbon nitride. Issue 8 (17th February 2021) - Zhao, Zhengyan; Liu, Wei; Shi, Yantao; Zhang, Heming; Song, Xuedan; Shang, Wenzhe; Hao, Ce
Abstract : The schematic diagram of the reaction mechanism of the g-C3 N4 catalyst for the CO2 RR. Abstract : We report a combination of experimental and computational mechanistic studies for the photoreduction of CO2 to CO with water, catalyzed by single-atom Fe supported on graphitic carbon nitride (g-C3 N4 ). Density functional theory (DFT) and time-dependent DFT (TDDFT) methods were utilized to explore the behavior of single-atom Fe in g-C3 N4, which is of vital importance to the understanding of the CO2 reduction reaction (CO2 RR) mechanism. The calculation results reveal that the rate-limiting step of the hydrogen-bonded complex in the absence of Fe atoms is the cleavage of C–O bonds in COOH radicals during the whole CO2 RR, which includes the photophysical and photochemical processes. The presence of Fe atoms not only activated CO2 in the ground state and increased the rate constant of the limiting step in the photophysical process, but also functioned as the catalytic active center, lowering the reaction barrier of the C–O bond cleavage in COOH˙ in the photochemical process and resulting in improved photocatalytic activity. In addition, DFT calculations further demonstrated that the electron and proton transfer involved in the photophysical and photochemical processes is closely related to and induced by the hydrogen bonds in the excited state.